Auditors Brainstorming Effort in Detecting Fraud: Indonesian Government Case - Agil Novriansyah, Yusnaini, Rina Tjandrakirana, Ermadiani, Ahmad Subeki, (Opción, 2019)
This study examines the effects of fraud type and accountability on internal auditor brainstorming effort for fraud detection. Data analysis conducted by the use of one-way ANOVA and independent sample t-test as a method. The results show that there are no significant differences brainstorming effort for internal auditors to detect fraud among either the three types of fraud or accountability pressure. In conclusion, pertaining to the role of accountability pressure, review of the auditor’s performance is required in order for the internal auditors to have greater effort in detecting fraud.